The 6-month effectiveness of Internet-based guided self-help for depression in adults with Type 1 and 2 diabetes mellitus - Ebert, David; Nobis, S.; Lehr, D.; Baumeister, H.; Riper, H.; Auerbach, R. P.; Snoek, F.; Cuijpers, P.; Berking, Matthias (Diabetic Medicine, 2017)
Conclusions The trial indicates that Internet-based guided self-help treatments for depression in people with diabetes can have sustained effects on depressive symptoms, well-being and emotional distress associated with diabetes.